DETERMINATION OF NORMAL CEPHALOMETRIC PARAMETERS BY J. MCNAMARA METHOD FOR UKRAINIAN BOYS AND GIRLS - Gunas І.V.; Dmitriev, M.O.; Tikholaz, V.O.; Shinkaruk-Dykovytska М.М.; Pastukhova, V.A.; Melnik М.Р.; Rudiy, Yu.I. (World of Medicine and Biology, 2018)
The article presents the cephalometric parameters used in cephalometric analysis by the J. McNamara method in boys and girls of Podillia region of Ukraine with orthognathic occlusion, evaluation of sexual differences of these parameters (in boys established significantly higher values of most indicators that characterize the ratio between the upper and lower jaw, and in girls - only a basic angle) and a comparison of the results with the data received by J. McNamara. It is shown that almost half of the cephalometric parameters obtained in Podillia boys and girls with orthognathic bite have distinct differences with the magnitude of these parameters obtained by J. McNamara